Halogen bonding : fundamentals and applications - Metrangolo, P. (Springer, 2017)
Theoretical characterization of the trends in halogen bonding / A. Karpfen -- The interaction of dihalogens and hydrogen halides with Lewis bases in the gas phase : an experimental comparison of the halogen bond and the hydrogen bond / A.C. Legon -- Halogen bonding with dihalogens and interhalogens / W. Pennington [and others] -- Halogen bonding in crystal engineering / P. Metrangolo [and others] -- X-ray structures and electronic spectra of the [pi]-halogen complexes between halogen donors and acceptors with [pi]-receptors / S.V. Rosokha and J.K. Kochi -- Halogen-bonded liquid crystals / D.W. Bruce -- Halogen bonding in conducting or magnetic molecular materials / M. Fourmigué.